Avrupa Birliği’ne uyum sürecinde Türk endüstri ilişkileri sistemi - Şeneldir, M. Yasin (My University, 2003)
In its early years the Member States of European Communities did not think of developing a common social policy. Later on a social model that was based on social state had been improved. In the field of social policy which was left to members own responsibility, the European Union deals only with matters where an EU solution makes more sense. Narrowing has seen in Turkish Industrial Relations Systems because of the effects of liberal policies that was applied after 1980. Particularly by the impacts of crises which was lived in 1990's and the international competition that was increased after Customs Union, there has been a regression in trade union struggle; the workers has been more jointer and become more agreeing. In recent years the workers, who are anxious about the protection of belongings, got their gains in the period of adaptation to the European Union. The gains like the job security, unemployment insurance, the right of public servants unionisation were put on the agenda in this period. This study explains the condition of the Turkish Industrial Relations Systems during the period of adaptation to the European Union. In this context the social policies of the EU and Turkey's arrangements to adapt EU acquis are examined. To obtain peace in working life, the arrangements that is related to social policies, must be made with the social partners consensus and for the purpose of Turkish Society's own dynamics requires them. Avrupa Topluluklarının ilk yıllarında üye devletler ortak bir sosyal politika geliştirmeyi düşünmemişlerdir. Zamanla temeli sosyal devlet ilkesine dayalı bir sosyal politika modeli geliştirilmiştir. Üye devletlerin asli sorumluluğuna bırakılan sosyal politika alanında AB, ikincillik ilkesine bağlı kalarak, sadece bir AB çözümünün daha anlamlı olduğu konularla ilgilenmiştir. 1980 sonrası uygulan liberal politikaların etkisiyle Türk Endüstri İlişkileri Sistemi'nde bir daralma yaşanmıştır. Özellikle 1990'lı yıllarda yaşanan krizlerin ve Gümrük Birliği'nden sonra artan uluslararası rekabetin etkileriyle sendikal mücadelede bir gerileme gerçekleşmiş; çalışanlar daha uzlaşmacı ve işbirlikçi bir yol arayışına girmişlerdir. Son yıllarda var olanı koruma kaygısı taşıyan çalışanlar, yeni kazanımlarını ancak Avrupa Birliği'ne uyum sürecinde elde edebilmişlerdir. İşsizlik sigortası, kamu görevlilerinin sendikalaşma hakkı, iş güvencesi gibi kazanımlar bu dönemde gündeme gelmiştir. Bu araştırma, AB'ye uyum sürecinde Türk Endüstri İlişkileri Sisteminin durumunu incelemektedir. Bu bağlamda Avrupa Birliği'nin sosyal politikaları ve Türkiye'nin AB Müktesebatına uyum için yaptığı düzenlemeler ele alınmıştır. Çalışma hayatında barışın sağlaması için sosyal politikalarla ilgili düzenlemeler, Türk toplumunun kendi dinamikleri gerektirdiği için ve sosyal tarafların mutabakatı sağlanarak yapılmalıdır.
Keywords: Avrupa Birliği; Endüstriyel İlişkiler